1995
DOI: 10.1111/j.1346-8138.1995.tb03922.x
|View full text |Cite
|
Sign up to set email alerts
|

Pustular Psoriasis Precipitated by Acetazolamide

Abstract: We report a case of pustular psoriasis precipitated by acetazolamide, a carbonic anhydrase inhibitor. A 28-year-old man suffering from 20 years-standing generalized pustular psoriasis developed psoriatic arthritis and glaucoma and experienced a precipitation of pustular lesions and widespread erythema after initiation of oral acetazolamide for glaucoma. The cutaneous lesions and systemic symptoms improved after restriction of acetazolamide and administration of oral etretinate. Readministration of acetazolamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Regarding carbonic anhydrase inhibitor eye drops, the reported psoriasis and lichenoid eruption cases appear chronologically relevant, with positive rechallenge, but the mechanism is unknown, and only one case involving systemic acetazolamide has been reported in the literature. 134 However, it is worth noting that among the few generalized eruptions reported in association with anti-glaucoma eye drops, two cases of erythema multiforme 122,123 and two cases of toxic epidermal necrolysis 120,121 had dorzolamide eye drops in common. Although scarce, these data invite us to consider nonsystemic drugs in severe cutaneous adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding carbonic anhydrase inhibitor eye drops, the reported psoriasis and lichenoid eruption cases appear chronologically relevant, with positive rechallenge, but the mechanism is unknown, and only one case involving systemic acetazolamide has been reported in the literature. 134 However, it is worth noting that among the few generalized eruptions reported in association with anti-glaucoma eye drops, two cases of erythema multiforme 122,123 and two cases of toxic epidermal necrolysis 120,121 had dorzolamide eye drops in common. Although scarce, these data invite us to consider nonsystemic drugs in severe cutaneous adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…24 It is also seen that pustular psoriasis has been precipitated by acetazolamide, a CA inhibitor, when used for glaucoma in some psoriatics. 25 Recently it has been suggested that increased reactive oxygen species (ROS) production and deficient function of antioxidant systems activities may be involved in the pathogenesis of the disease. 26 The carbonic anhydrase enzyme has recently been reported to have an anti-oxidant activity, which is glutathione- Original Article NJDVL -21 mediated.…”
Section: Introductionmentioning
confidence: 99%